Gandhian Philosophy: A Relevance of Swadeshi - Dr. Ram Ratan Sahu; Kamalika Hawldar (Jai Maa Saraswati Gyandayini An International Multidisciplinary e-Journal, 2017)
Gadhian philosophy of life was a holistic one. He looked upon life as a supreme value and an indivisible whole. Gandhi integrated the different fact of life and believed in the inner unity of life and oneness of all creations. It was his firm conviction that law governing the conduct and life of human species and of the universe is the law of truth and the path leading to it is the principle of non-violence or love. The only way to realize the grand and noble aim of life is to organize all activities of life on the basis of twin principle s of truth and non-violence. It will be difficult to take all aspects of life in one go for a systematic analysis. But it is always, necessary to be aware that we are concentrating on a piece of the whole, one at a time, and it is the whole we are aiming at. At present we are contemplating on one aspect of Gandhian Philosophy, that is Swadeshi. Swadeshi is an integral part of Gandhian economies. Gandhian economics is nothing but an economics of love or non-violence. Our main concern should be how to organize our lives according to the law of human species. Swadeshi, trusteeship, decentralized mode of production etc. are parts of the magnificent and grand life which Gandhi wanted to achieve for all members of the society including the downtrodden.